A Fuzzy Logic Approach to Explaining Aggregate Investment in Indonesia, Malaysia, Thailand and Philippines - Kan, Chung Yan (2008)
Interest rate is often regarded as one of the key factors affecting fixed investment. This paper studies the impact of the real interest rate on aggregate investments in four of the Southeast Asian countries- Indonesia, Malaysia, Thailand and Philippines from 1995 to 2003 using a non-linear fuzzy logic. Fuzzy logic is ideal for modeling human decision making in an intuitive manner. Linstrom (1998) first applied fuzzy logic approach to investigate the relationship between real interest rate and aggregate investments in Sweden. In his approach, a multivalued logic and a fuzzy indicator are strictly derived from the interest rate.